Co-microencapsulation of γ-aminobutyric acid (GABA) and probiotic bacteria in thermostable and biocompatible exopolysaccharides matrix. (January 2021) - Pandey, Pooja; Mishra, Hari Niwas
Abstract: In this study, a bioactive neurotransmitter commonly known as γ-aminobutyric acid (GABA), and a probiotic Lactobacillus plantarum (LP) were co-encapsulated using spray drying in a biocompatible matrix composed of inulin, dextran, and maltodextrin. The effects of each wall material on the physicochemical characteristics of microcapsules such as moisture content, GABA content, flowability, bulk, and tapped density were evaluated. The optimum shell composition obtained by D-optimal mixture design was 0.4%, 4.6%, and 8.4% of inulin, dextran, and maltodextrin respectively. The optimum formulation exhibited maximum GABA and LP encapsulation efficiencies of 84.22% and 99.21% respectively, along with a desirability of 0.86. The microcapsules maintained a spherical morphology with particle size in the range of 10–35 μm, as determined from SEM and optical microscopic images. The FTIR analysis confirmed that inulin, dextran, and maltodextrin retained their native chemical structure in the microcapsules even after spray drying. The TGA results revealed that the produced microcapsules were highly thermostable. Furthermore, no significant differences (p < 0.05) in the viability of bacteria and GABA retention was found after 120 days of storage at 4 °C. Thus, the microcapsules offer GABA, probiotics, and prebiotics in a single multifunctional platform for delivery through various food matrices. Highlights: Lactobacillus plantarum and GABA encapsulated multicore microcapsules were prepared by spray drying technology. Dextran, Inulin and maltodextrin were used as wall materials. Wall material formulation was optimized using D-optimal mixture design. Microcapsules with dextran and inulin as wall material showed highest encapsulation efficiency.